The gut-brain connection: Exploring the influence of the gut microbiota on neuroplasticity and neurodevelopmental disorders. (15th June 2023) - Damiani, Francesca; Cornuti, Sara; Tognini, Paola
Abstract: Neuroplasticity refers to the ability of brain circuits to reorganize and change the properties of the network, resulting in alterations in brain function and behavior. It is traditionally believed that neuroplasticity is influenced by external stimuli, learning, and experience. Intriguingly, there is new evidence suggesting that endogenous signals from the body's periphery may play a role. The gut microbiota, a diverse community of microorganisms living in harmony with their host, may be able to influence plasticity through its modulation of the gut-brain axis. Interestingly, the maturation of the gut microbiota coincides with critical periods of neurodevelopment, during which neural circuits are highly plastic and potentially vulnerable. As such, dysbiosis (an imbalance in the gut microbiota composition) during early life may contribute to the disruption of normal developmental trajectories, leading to neurodevelopmental disorders. This review aims to examine the ways in which the gut microbiota can affect neuroplasticity. It will also discuss recent research linking gastrointestinal issues and bacterial dysbiosis to various neurodevelopmental disorders and their potential impact on neurological outcomes. This article is part of the Special Issue on "Microbiome & the Brain: Mechanisms & Maladies". Graphical abstract: Image 1 Highlights: Signals coming from the gut microbiota could influence neuroplasticity. Gut microbiota could affect brain gene expression, neurotransmitters, and microglia. Dysbiosis in early stages of life may interfere with neurodevelopmental trajectories. Microglia activation may be linking gut dysbiosis to altered plasticity. Neurodevelopmental disorders symptoms may be ameliorated via microbial manipulation.